Mercury isotope profiles against the massive dissolved organic carbon remineralization for the largest Ediacaran carbonate-carbon isotope excursion - Xi, Pengfei; Liu, Yongsheng; Chen, Jiubin; Shen, Jun (Earth and planetary science letters, 2024)
•Limited contribution of organic carbon to the Shuram Excursion.•The enhanced terrestrial input and the photic zone euxinia reduced the Δ199Hg.•The photic zone euxinia frequently occurred in the mid-depth ocean.•Macroscopic multicellular eukaryotes were poisoned by H2S. The Doushantuo negative carbon isotope excursion (DOUNCE), which corresponds to the worldwide mid-Ediacaran Shuram-Wonoka anomaly (567∼574 Ma), is characterized by a significant shift in carbonate-carbon isotopic values (δ13Ccarb) from ∼ 5‰ down to ∼ -12‰. It has been proposed to result from remineralizing a giant dissolved organic carbon (DOC) pool within the Ediacaran Ocean. However, direct geological proof confirming the existence and oxidation of such a large DOC reservoir is still scarce. The strong affinity of Hg for organic carbon in the surface environment could provide helpful information on the potential contribution of Hg-associated DOC to the DOUNCE. Here, Hg content and isotope values of marine sediments from the slope (Songtao) and basin (Fengtan) settings were measured and discussed with the previously published data from the shelf environment (Jiulongwan) in South China. The generally low Hg concentration and the absence of Hg/TOC (total organic carbon) anomaly within the DOUNCE carbonate from the proximal to distal sections argue against the massive contribution of DOC to the DOUCE. The gradually decreasing Δ199Hg but increasing δ202Hg in the proximal depositions would be indeed ascribed to the enhanced terrestrial input and the photic zone euxinia (PZE), which might hinder the development and expansion of macroscopic multicelluar eukaryotes via H2S poisoning. Our new Hg isotope data casts doubt on the DOC oxidation model, and contributions from other 12C-enriched reservoirs (e.g. recycled carbonatites) could be the cause of the most significant negative δ13Ccarb excursion in Ediacaran.